2016
DOI: 10.1097/mop.0000000000000427
|View full text |Cite
|
Sign up to set email alerts
|

The role of the gut microbiota in food allergy

Abstract: Progress in understanding the role of dysbiosis in food allergy and the factors that promote its development, such as antibiotic therapy, diet, modes of infant delivery, and environmental exposures, offer windows of opportunity for both preventive and therapeutic interventions to stem the rising tide of the food allergy epidemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(48 citation statements)
references
References 60 publications
2
45
0
1
Order By: Relevance
“…As reported previously by us [27], fish oil supplementation in utero was associated with enhanced expression of PKCζ in the CB T-cells, perhaps providing an explanation for the protection against allergic responses. Although the validity of the hygiene hypothesis has recently been called into question [55], our data may also contribute to the understanding of the basis for the protection from allergic diseases that is associated with microbial exposure early in life [56,57]. We have previously reported that polyclonal stimulation of CB T-cells with PHA increased the level of PKCζ [22].…”
Section: Discussionmentioning
confidence: 84%
“…As reported previously by us [27], fish oil supplementation in utero was associated with enhanced expression of PKCζ in the CB T-cells, perhaps providing an explanation for the protection against allergic responses. Although the validity of the hygiene hypothesis has recently been called into question [55], our data may also contribute to the understanding of the basis for the protection from allergic diseases that is associated with microbial exposure early in life [56,57]. We have previously reported that polyclonal stimulation of CB T-cells with PHA increased the level of PKCζ [22].…”
Section: Discussionmentioning
confidence: 84%
“…Intestinal microbiota regulate the development of functions of a diverse range of T cells, such as Th17, Th1, Th2, and regulatory T cells, and also modulate innate lymphoid cells [33,34]. By modifying the response of gut-associated lymphoid tissues, intestinal microbiota may influence the development of oral tolerance [35].…”
Section: Discussionmentioning
confidence: 99%
“…Food allergy is one of the most common allergies in infants and children, the prevalence rate of which is increased with time for foods including cow milk protein (1). The prevalence of cow milk protein allergy (CMPA) has been reported to be increased from 1.6% to 3.5% over a decade (2).…”
Section: Introductionmentioning
confidence: 99%